Interplay between pi-bridges and positions of branched alkyl groups of unsymmetrical D-A-D-pi-A squaraines in dye-sensitized solar cells: mode of dye anchoring and the charge transfer process at the TiO2/Dye/electrolyte interface - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Far-red-absorbing squaraines possessing high molar absorptivity (>10(5) M-1 cm(-1)) are being attracted as high-efficiency chromophores in dye-sensitized solar cells (DSSCs). A series of donor acceptor -donor-pi spacer-acceptor (D-A-D-pi-A) unsymmetrical squaraines, PSQ1-5, with indoline donor and squaric/cyanoacetic acid acceptor units, were designed for sensitized solar cells. For extending the absorption toward the near-infrared region (NIR) and controlling the orientation on the TiO2 surface, benzene (PSQ1 and PSQ2) and thiophene (PSQ3-5) 7r-spacers and out-of-plane branched alkyl groups at the indoline that are away (PSQ1, PSQ3, and PSQS) or near (PSQ2 and PSQ4) the anchoring group, respectively, were introduced. Dynamic aggregation tendency of PSQ1 and PSQ3 than that of their isomers systematically modulates the orientation on the TiO2 surface, which in turn enhances photovoltaic performance. Absorptance on a thin transparent TiO2 film shows a visible-to-NIR response with an onset around 800 nm for PSQ3-5. Although there is resemblance in electrochemical redox levels, their high injection efficiency and recombination resistance differentiated impact on the way of anchoring and the dihedral angle between D-A-D units and g-spacers. DSSCs sensitized with PSQS achieved a PCE of 8.15% under simulated AM 1.5G illumination (100 mW cm(-2)), with the current density (j) and open-circuit voltage (Voc) of 19.73 mA cm(-2) and 630 mV, respectively. A clear comparison of the incident-photon-to-current conversion efficiency versus the light-harvesting efficiency correlates the structure-property relationship with J obtained for PSQ dyes. Electrochemical impedance spectroscopy was carried out to examine the TiO2/dye/electrolyte interface for further confirmation of the enhanced PCE of top-se-alkylated PSQS over that of other dyes.
Keywords: D-A-D-pi-A framework; dye-sensitized solar cell; H- and J-type aggregation; orientation of dyes; static/dynamic aggregates; unsymmetrical squaraine

Effect and position of spiro-bipropylenedioxythiophene pi-spacer in donor-pi-spacer-acceptor dyes for dye-sensitized solar cell - Sil, Manik Chandra; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Dyes and Pigments, 2019)
Improper orientation and self-assembly of dyes on TiO2 surface are the main disadvantages at the dye-TiO2 interface that governs both charge injection and dye regeneration processes. In this report, a series of homo spiro-dimeric donor-pi-spacer-acceptor (D-pi-A) dyes based on bithiophene and terthiophene spacers with two-anchoring group containing dyes, TT1, T1T, TT1T were designed and synthesized by Pd-catalyzed successive Suzuki coupling followed by direct arylation reactions. The position of branching centre in TT1 and T1T was systematically varied, where the spiro unit was placed near and away from the anchoring carboxylic acid unit, respectively. The dimeric spiro-dye T1T showed device performance, which is 1.6 fold higher than its structural isomeric analogue TT1, of 3.9% with a V-oc and J(sc) of 0.593 V and 9.09 mA/cm2, respectively, whereas for the isomeric analogue TT1 a device performance of 2.45% (V-oc of 0.568 V and J(sc) of 6.25 mA/cm2) under simulated 1 Sun (100 mW/cm2) condition. The improved Voc for the dye T1T compared to TT1 dye was ascribed to the dipole moment exerted by the dyes on TiO2 surface. Further the PCE of 4.16% (V-oc 0.589 V, J(sc) 9.79 mA/cm2 respectively) maximum was observed, when an extra thiophene unit was inserted in between the donor and pi-spacer in dye TT1T. The shifting the position of branching spiroBiProDOT pi-spacer makes an impact on the device performance by synergistically enhancing both Voc and Jsc.
Keywords: CDCA; D-pi-A Spiro dye; Dye aggregation; dye-sensitized solar cell; spiroBiProDOT spacer

Aniline and indoline donors based far-red active unsymmetrical squaraine dyes for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2024)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on the metal-oxide surface by appending the alkyl groups around the donor or pi-spacer unit of the dye is a potential approach to enhance DSSC efficiency. Further, rigidification of the dye structures by cyclization modulates the photophysical properties of the sensitizer. Here a series of donor-acceptor-donor (D-A-D) type far-red active unsymmetrical squaraine dyes (SQA) have been designed and synthesized, where N,N-dimethylaniline, methylated- and branched-indoline have been used as donor units. These dyes showed absorption between 629-654 nm (lambda max) with the molar extinction coefficient of 1.49-1.94x105 M-1 cm-1. Systematic enhancements in DSSC device efficiency have been observed due to the cyclization and alkyl-groups incorporation in this set of dyes which were further enhanced with the addition of chenodeoxycholic acid (CDCA). The highest DSSC device efficiency of 4.78 % (Jsc of 8.77 mA/cm2 and Voc of 692 mV) has been achieved for SQA3. The IPCE profile of SQA dyes indicates the contribution of aggregated structures for the photocurrent generation. Further, co-sensitization of SQA3 dye with a complementary visible light active dye AK4 showed the enhanced device efficiency of 6.27 % with panchromatic IPCE response. Dye rigidification, and controlled aggregation of dyes on TiO2 by means of cyclization of donor unit and introducing the alkyl groups in the dye structure synergistically improve the dye-sensitized solar cell (DSSC) device performance. Donor-Acceptor-Donor (D-A-D) based unsymmetrical squaraine dye SQA3 showed the DSSC device performance of 4.78 %.image
Keywords: co-sensitization; dye-sensitized solar cell; effect of alkyl chain; molecular planarity; squaraine dye

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye